Straggler Problem –Tail Latancy in Distributed network - Rahman, Md. Nesar; Siddika, Ayesha; Islam, Muhammad Shafiqul; Shahajada, Md (International Journal of Computer Sciences and Engineering, 2019)
Distributed processing frameworks split a data intensive computation job into multiple smaller tasks, which are then executed in parallel on commodity clusters to achieve faster job completion. A natural consequence of such a parallel execution model is that slow running tasks, commonly called stragglers potentially delay overall job completion. Stragglers in general take more time to complete tasks than their peers. This could happen due to many reasons such as load imbalance, I/O blocks, garbage collections, hardware configuration etc. Straggler tasks continue to be a major hurdle in achieving faster completion of data intensive applications running on modern data-processing frameworks. The trouble with stragglers is that when parallel computations are followed by synchronizations such as reductions, this would cause all the parallel tasks to wait for others meaning that the parallel runtime is dominated by the slowest performing straggler. In a large-scale distributed system comprising a group of worker nodes, the stragglers` delay performance bottleneck, is caused by the unpredictable latency in waiting for slowest nodes (or stragglers) to finish their tasks. Such stragglers increase the average job duration by 52% in data clusters of Facebook and Bing even after these companies using state of the art straggler mitigation techniques[1]. This is because current mitigation techniques all involve an element of waiting and speculation. Existing straggler mitigation techniques are inefficient due to their reactive and replicative nature – they rely on a wait speculate- execute mechanism, thus leading to delayed straggler detection and inefficient resource utilization. Hence, full cloning of small jobs, avoiding waiting and speculation altogether is proposed in a system called as Dolly. Dolly utilizes extra resources due to replication.